Influence of intercropping on soil properties and nutrient status of fruit based agroforestry systems in north Western region of Indian Himalaya - Zahoor, Shiba; Dutt, Vaishnu; Mughal, A.H.; Pala, Nazir A.; Rashid, Megna; Khan, P.A. (Indian Journal of Agroforestry, 2022)
ABSTRACT: Healthy soil is perhaps the most basic assets for the ecosystem wellbeing and sustainability, including agro ecosystems. Although the agroforestry community has for long been persuaded of the benefits of healthy soil of agroforestry practices, a significant number of such practices stay to be completely acknowledged by the mainstream agriculture community. The present study was carried out at farmer’s field in central Kashmir region of India. The experiment was spread out in a randomized block design with five replications comprising of seven treatments. For conducting the study four intercrops viz., rajmash (Phaseolus vulgaris), green gram (Vigna radiata), french bean (P. vulgaris) and oats (Avena sativa) were intercropped with 11 year old orchard of apple planted at spacing of 4 x 4 m. Fruit based land system showed significantly higher values of pH, organic carbon (OC %), available N, P and K than agriculture land use. A maximum value of soil carbon (1.74 %) was observed in apple + rajmash and oats and apple + green gram and oats followed by apple + french bean and oats (1.65 %). Overall highest values of soil moisture, available N, P and K were observed under apple based agroforestry land use than mono cropping systems. Highest value of soil moisture (12.86 %) and available N (387.35 kg ha-1) was observed under agroforestry system of apple + green gram and oats. The treatment, apple + rajmash and oats displayed highest values for both available P (19.85 kg ha-1) and available K (224.58 kg ha-1). The highest soil organic carbon was stored in the treatment involving the tree combination of apple + green gram and oats (46.02 t ha-1) and is around 1.15 to 1.38 times higher than agriculture based land use system. The light transmission ratio (%) of 100 % was recorded under agroforestry systems whereas minimum (59.95 % and 74.63 %) was displayed for pulses and oats respectively. The reduction in light transmission ratio was more up to D1 (78.17% and 85.25%) in comparison to D2 (81.09% and 89.15%) for pulses and oats respectively. From the study it can be very well reasoned that tree based land use frameworks of temperate zone of the Himalayan region are more sustainable and environment benevolent than agriculture based land use system.